Impact of Academic Social Network Engagement on University Lecturers’ Research Output and Professional Development (Fountain Journal of Natural and Applied Sciences, 2022)
The impact of quality academic publications and training attended on the productivity of an academic member cannot be overemphasized. Its impacts extend beyond just the growth of an academic member, it radiates to increasing University’s ranking among its comity. With the affordances provided by the Internet, academic social network (ASN) emerged as an Internet-based social networking community for academia to seek for research resources and exchange ideas that can assist in developing new knowledge for self-development and community at large. Grounded on the collaborative feature of ASN, researchers’ geographical gap can easily be bridged. Thus, the academia assumes that the research output (RO) and professional development (PD) of an academic member would gain greater quality. Consequent on this assumption, this study examined the impact of ASN engagement on university lecturers’ RO and PD. It employed a quantitative research design of the survey type and sampled 350 academic members across three universities in Nigeria with a multistage sampling technique. A validated researchers-design questionnaire with a reliability value of 0.88 served as the research instrument. Descriptive statistics was explored as analytical tool. The outcome of the study provided insights into the adoption of ASN among academic members, with heavy emphasis on ASN for research purposes only, rather than on RO and PD respectively. This study recommends that there is a need for awareness and motivation towards the use of some ASN. Hopefully, this will further enhance their RO and PD, which will ultimately reflect on the quality of Nigerian graduate.Keywords: Academic Social Network, Engagement, Research Output, Professional Development, Internet
Keywords: Academic Social Network; Engagement; Research Output; Professional Development; Internet